Effects of Mo alloying on the microstructure and wear resistance of Fe–B surfacing alloys - Zhen Ma; Yuanhu Zhang; Liting Mu; Zhiqiu Huang; Kexin Di; Jianhui Su; Minghui Zhuang; Shidan Yuan; Longquan Wang (Journal of Materials Research and Technology, 2023)
The effect of Mo addition on microstructure, impact property, and wear resistance of high boron Fe-4.5 wt% B surfacing alloy, which was developed by the three-arc double-wire welding method was investigated in this work. The phase structure and microstructure of the surfacing alloy were studied by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), and Electron Backscattered Diffraction (EBSD). Besides, a two-body abrasive wear test and impact fracture test was carried out to study the wear behavior and fracture mechanism of the surfacing alloy. The results show, hypereutectic Fe-4.5 wt% B surfacing alloys with different Mo additions are mainly composed of primary (Fe, Mo)2B boride, eutectic matrix, and FeMo2B2. With the increase of Mo content in Fe-4.5 wt% B surfacing alloy, the continuous growth of the eutectic structure is blocked, which can inhibit the formation and expansion of cracks in the surfacing layer. With the increase of Mo, the wear resistance of Fe-4.5 wt% B alloy increases from 16.70 g-1 to 22.72 g-1. In the impact fracture experiment, Fe-4.5 wt% B surfacing alloy has high brittleness, the primary Fe2B is a transgranular fracture, and the interface between primary Fe2B boride and eutectic structure is an intergranular fracture. With the addition of Mo, the fracture mechanism of the surfacing alloy changes from transgranular fracture to transgranular fracture + ductile fracture, which reduces the fragmentation and spalling during the wear process, thereby improving its wear resistance.